The Quality of Work-Life and Work Comfort of Librarians During the Covid-19 Pandemic - Fatmawati, Endang (Daluang: Journal of Library and Information Science, 2021)
Background/purpose. This research aims to determine the quality of work-life and comfort of librarians during the Covid-19 pandemic. The intention was to provide input and reports to the leadership by mapping the performance of librarians.Methods. Consequently, thirteen informants were chosen, with the criterion that they were librarians working in the Library of the Faculty of Economics and Business, Diponegoro University. Interviews were used to collect the data, which were analyzed using qualitative descriptive methods.Results. Subsequently, the results showed that ten parameters of quality of work-life affect the comfort of librarians working during the Covid-19 pandemic.Conclusions. The convenience of working was revealed as the main goal in improving the library environment. Also, working from home or the office was shown as capable of creating a sense of satisfaction, thereby improving the quality of work-life. This quality, specifically during the pandemic, has become a collection of the perceptions of a sense of comfort at work, with conditions of continued growth and development to improve performance.